The Plasmodium falciparum Artemisinin Susceptibility-Associated AP-2 Adaptin μ Subunit is Clathrin Independent and Essential for Schizont Maturation - Henrici, Ryan C. (mBio, 2020)
The efficacy of current antimalarial drugs is threatened by reduced susceptibility of Plasmodium falciparum to artemisinin, associated with mutations in pfkelch13. Another gene with variants known to modulate the response to artemisinin encodes the μ subunit of the AP-2 adaptin trafficking complex. To elucidate the cellular role of AP-2μ in P. falciparum, we performed a conditional gene knockout, which severely disrupted schizont organization and maturation, leading to mislocalization of key merozoite proteins. AP-2μ is thus essential for blood-stage replication. We generated transgenic P. falciparum parasites expressing hemagglutinin-tagged AP-2μ and examined cellular localization by fluorescence and electron microscopy. Together with mass spectrometry analysis of coimmunoprecipitating proteins, these studies identified AP-2μ-interacting partners, including other AP-2 subunits, the K10 kelch-domain protein, and PfEHD, an effector of endocytosis and lipid mobilization, but no evidence was found of interaction with clathrin, the expected coat protein for AP-2 vesicles. In reverse immunoprecipitation experiments with a clathrin nanobody, other heterotetrameric AP-complexes were shown to interact with clathrin, but AP-2 complex subunits were absent.